Analisis Kadar Pemanis Buatan pada Suplemen Anak dengan Metode Kromatografi Cair Kinerja Tinggi (KCKT) dan Spektrofotometri UV-Vis - Puspitasari, Lia; Thalib, Amlius; Finanti, Hanif Mifta (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Sweeteners are food additives in the form of natural sweeteners and artificial sweeteners that give a sweet taste to food products. The use of sweeteners that are not in accordance with the limits set can have a negative impact on health. This study aims to determine whether the levels of artificial sweeteners in the form of saccharin and cyclamate in children's supplements have met the requirements set by BPOM according to the Decree of the Head of BPOM No. 12 of 2014 and Circular Letter No. HK.04.01.42.421.12.17.1666 of 2017 concerning Limits. Maximum Permitted Use of Artificial Sweeteners in Traditional Medicinal Products and Food Supplements. Three samples of children's supplements were taken randomly at several drug stores. The research method used for the determination of saccharin levels using HPLC and the determination of cyclamate levels using UV-VIS spectrophotometer The results of the analysis of saccharin levels are; sample (1084) = 463.02 mg/kg, sample (1085) = 363.01 mg/kg, and sample (1114) = 652.61 mg/kg. As for the levels of cyclamate obtained, sample content (1084) = 763.34 mg/kg, sample (1085) = 1279.87 mg/kg, and sample (1114) = 436.07 mg/kg. In conclusion, all samples tested for saccharin levels met the requirements for the maximum limit of 1000 mg/kg set by BPOM. Meanwhile, the sample (1085) tested for cyclamate did not meet the requirements for the maximum limit of 1250 mg/kg set by BPOM.